The Effect of Variation in the Number of Pole and Air Gap on Torque Density on Radial Magnetic Spur Gear with Magnetic Block - Agus Sigit Pramono; Alfiana N Hidayati (JMES: The International Journal of Mechanical Engineering and Sciences, 2020)
Magnetic gear is an alternative to mechanical gear, where the magnetic gear has the advantages of no noise, minimum vibration, no maintenance required, increased reliability, overload protection capability, no physical contact between gears, and the resulting torque density is still below the mechanical gear torque density. In this research, the variation of the number of poles and air gap in the amount of torque density produced was carried out. The permanent magnet material used is Neodymium type with a gear ratio of 1:2. In the variation of the number of poles used by pairs of 4 and 8 poles, 8 and 16 poles, 10 and 20 poles, and 12 and 24 poles, in the variation of the air gap used, namely 1 mm, 1.2 mm, 1.3 mm, 1.4 mm and 1.5 mm. Magnetic gear performance can be seen through analysis simulation with the 3D finite element method using Finite Elements Software. The type of simulation used is the magnetostatic analysis method at the processing stage and the transient analysis method at the post-processing stage. From the simulation results, it is concluded that the greater the number of poles, the greater the torque density produced, and the closer the air gap distance will result in a greater torque density. The effect of the number of poles on the torque density is more significant than the effect of the air gap.